THE CLINICAL EXAMINATION- LONG CASE. THE MOST VALID TEST IN A MEDICAL SCHOOL - Mirghani, Omer Ahmed; Elsanousi, Mohammed (Gezira Journal of Health Sciences; Vol 4 No 1 (2008), 2008)
This article reflects the cumulative experiences of all the teachers- particularly the clinicians- in the Faculty of Medicine University of Gezira (FMUG) since its foundation in 1978. It also includes some of the comments of a large number of renowned external examiners who participated in the clinical examinations.